2003
DOI: 10.1007/978-3-540-40012-7_10
|View full text |Cite
|
Sign up to set email alerts
|

Scheduling and Quality Differentiation in Differentiated Services

Abstract: During the last decade the Internet has developed into a public multi service network that should be able to support heterogeneous applications and customers with diverse requirements. For this reason, quality of service (QoS) provisioning in the Internet has gained increasing attention.General service architectures have been proposed in the literature for providing QoS. At the moment, the Dierentiated Services (DiServ) architecture seems to be the most promising solution due to its scalability. In DiServ, com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Our previous studies [6], [7], [8], concentrated on finding out the best combinations on traffic groupings from QoS perspective. These simulations have shown that the right amount of traffic classes is three or four.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous studies [6], [7], [8], concentrated on finding out the best combinations on traffic groupings from QoS perspective. These simulations have shown that the right amount of traffic classes is three or four.…”
Section: Resultsmentioning
confidence: 99%